Decision making in the family business: need for a reorganization based on corporate governance - Arbulú Celi, Juan Antonio (2021)
Family businesses, are the largest number of companies in the country, and a large number of them still have a precarious management, marked by custom and the ways in which the founders made decisions, lacking structures that allow their permanent growth and, above all, their survival over time, relegating their success. The other component present in this work is Corporate Governance (here in after CG), understood as that system of management, supervision and control of organizations, which seeks to improve their structure and organization, their decision-making process, information management, supervision and control of operations. As I have pointed out, one of the shortcomings of family businesses, which constitutes an obstacle to their development, is the way in which they make decisions, since the "family" component has too much influence, with the feelings and close relationships that are involved, often causing business decisions to have a sentimental and not an objective basis, and that is when the decision crises begin. In view of the above, this paper intends to propose that a restructuring of the governance system in these companies is necessary to improve and make the decision-making process more efficient. The study design will be experimental and qualitative classification, that is, it will be handled on the practical intervention based on the experience of a family business in which good corporate governance practices are implemented to improve its decision-making process. And qualitative insofar as modifications of variables are allowed during implementation, given the particular characteristics of the company.